A detailed study on adsorption isotherms of Hg(II) removal from aqueous solutions using nanostructured sorbent ZnCl2-MCM-41. Issue 40 (26th August 2016) - Raji, Foad; Pakizeh, Majid; Saraeian, Alireza; Raji, Mojtaba
Abstract: A comparison between linear and non-linear regression methods to determine the optimum isotherm was done by applying these models to the experimental equilibrium data of Hg(II) sorption using new nanostructured sorbent ZnCl2 –MCM-41. The best-fitting linear isotherm was selected based on the highest R 2 value obtained. In the case of non-linear methods, different error functions were employed to determine the best-fitting model. Langmuir isotherm was found to be the best-fitting model in both linear and non-linear cases, which implies a monolayer adsorption of Hg(II) onto a homogeneous surface of ZnCl2 –MCM-41. Scanning electron microscopic images verified the spherical morphology of the sorbent particles. The adsorption capacities of Hg(II) onto CaCl2 –MCM-41, CuCl2 –MCM-41, and MgCl2 –MCM-41 were demonstrated to be less than those of ZnCl2 –MCM-41. Lastly, Hg(II) recovery of up to 75% was obtained by utilizing 0.1 M HNO3 solution.